Akun Instagram Parenting sebagai Media Edukasi Ketahanan Keluarga - Naiza Rosalia; Mutia Rahmi Pratiwi; Choirul Ulil Albab; Fibriyani Nur Aliya (Jurnal Riset Komunikasi (JURKOM), 2022)
Education about family resilience is essential to strengthen national unity. Family resilience in Indonesia is still considered lacking, especially during the pandemic the divorce rate is even higher. Social media, especially Instagram, has a significant role as the right educational media for the younger generation. The research was conducted to design media for family resilience education for the younger generation. This research is a qualitative study with a descriptive approach. Researchers conducted a content analysis on four family education Instagram accounts to get an idea of ??the information needs related to family resilience. Three crucial aspects of family resilience are physical resilience, resilience, social resilience, and psychological resilience. The analysis conducted on the @ibupedia.id, @parenting_islam.id, @parenttalk.id, and @talkparenting accounts revealed several sub-aspects of physical endurance, such as home ownership and work require more emphasis. In general, aspects of psychological resilience, such as managing emotions, stress, and household finances, are still not given much attention. These contexts are actually at the level of the husband and wife relationship, which should be the key to creating family resilience. The results of this study can be used as a reference for developing more comprehensive parenting education media.